2017
DOI: 10.1039/c7ra08696b
|View full text |Cite
|
Sign up to set email alerts
|

Protein-free ribosomal RNA folds to a near-native state in the presence of Mg2+

Abstract: The assembled bacterial ribosome contains around 50 proteins and many counterions. Here, focusing on rRNA from the large ribosomal subunit, we demonstrate that Mg 2+ causes structural collapse in the absence of ribosomal proteins. The collapsed rRNA forms many native-like RNA-RNA interactions, similar to those observed in the assembled ribosome. We assayed rRNA structure by chemical footprinting in the presence and absence of Mg 2+. Our results indicate that Mg 2+ -dependent conformational change is focused in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…SHAPE provides quantitative, nucleotide-resolution information about RNA flexibility, base pairing, and 3D structure, and has previously been used to monitor the influence of cations, small molecules, or proteins on RNA structure (27–32). We previously used SHAPE to show that the LSU rRNA adopts a near-native state in the presence of Mg 2+ , with the core inter-domain architecture of the assembled ribosome and residues positioned for interactions with rProteins (33). Here, SHAPE experiments were performed in an anoxic chamber to maintain the oxidation state of the metals and to prevent Fenton cleavage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHAPE provides quantitative, nucleotide-resolution information about RNA flexibility, base pairing, and 3D structure, and has previously been used to monitor the influence of cations, small molecules, or proteins on RNA structure (27–32). We previously used SHAPE to show that the LSU rRNA adopts a near-native state in the presence of Mg 2+ , with the core inter-domain architecture of the assembled ribosome and residues positioned for interactions with rProteins (33). Here, SHAPE experiments were performed in an anoxic chamber to maintain the oxidation state of the metals and to prevent Fenton cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…SHAPE (28, 32, 33) was conducted on the ~2900 nt Thermus thermophilus 23 rRNA (LSU) in 250 mM monovalent cation (Na + or K + ) to favor formation of secondary structure, and in 250 mM Na + or K + plus various divalent cation (10 mM MgCl 2 , 2.5 mM FeCl 2 , or 2.5 mM MnCl 2 ) to favor tertiary interactions. These divalent cation concentrations are sufficient to fold rRNA.…”
Section: Methodsmentioning
confidence: 99%
“…RNA compaction may play a role in packaging efficiency. It has been shown that a-rRNA 38 and 23S rRNA 42,43 fold to compact secondary and tertiary structures. We compared Qb VLP packaging of mRNA GFP -hp to a-rRNA-hp and 23S rRNA-hp.…”
Section: Effects Of Rna Length and Intrinsic Compaction On Packaging mentioning
confidence: 99%
“…Under pre-GOE conditions, Fe 2+ would not have caused the oxidative damage to biomolecules that occurs today in the presence of O 2 , via Fenton chemistry (22). We recently reported that Fe 2+ can mediate in vitro translation under “pre-GOE” conditions: in the presence of abundant Fe 2+ and in the absence of O 2 (23,24). Based on these findings, we proposed that early ribosomal folding and catalysis used Fe 2+ instead of, or in combination with Mg 2+ and other M 2+ ions.…”
Section: Introductionmentioning
confidence: 99%